Optimalisasi Pencahayaan Alami Terhadap Kenyamanan Visual: Simulasi Ruang Studio Arsitektur Menggunakan Geolokasi EPW D.I. Yogyakarta - Ingrid Vicaningrum; Syam Rachma Marcillia (Arsir: Jurnal Arsitektur, 2024)
Daylighting is a crucial element in workspace design, especially in architecture studios. Proper lighting not only improves productivity and comfort, but also has an impact on the health and visual well-being of space users. This research aims to evaluate the intensity of natural lighting entering the space to ensure that the lighting levels meet the visual comfort standards of the space users. This research method uses Sketchup, Rhino 7 and Grasshopper software simulations to see the distribution of incoming light in the architecture studio space by using the EPW coordinate geolocation of Yogyakarta and time to control natural light from east to west. The variables used in this evaluation are incoming light distribution, window size (WWR), wall material and color. The results of this study show that daylighting plays an important role in creating visual comfort in architectural studio workspaces, with the right lighting intensity of 350 - 750 lux based on Illuminating Engineering Society (IES) standards, thus having a positive impact on the visual well-being of studio space users. In addition, daylighting can provide a good strategy in improving the quality of architectural studio workspaces and directly contribute to improved performance and creativity. The benefits of this research evaluate daylighting on visual comfort in order to increase productivity at work, so that daylighting can be utilized as much as possible, and have a positive impact on the well-being of studio space users.